On evaluation codes coming from a tower of function fields - Carvalho, Cícero (2018)
In this work we present the construction of evaluation codes defined from data coming from a tower of function fields. We use tools from Gröbner basis theory to calculate the dimension and find a lower bound for the minimum distance of these codes.